Climate regimes, El Niño-Southern oscillation and konzo epidemics - Oluwole, Olusegun S. A. (Frontiers in Environmental Science, 2015)
Epidemics of konzo have occurred during severe droughts in parts of east, central, and southern Africa since the 1920s. Occurrence is attributed to exposure to cyanide from poorly processed cassava foods, the sole source of calories when other food crops fail. El Nino, the warm phase of the El Nino-Southern Oscillation (ENSO), induces severe droughts in the geographical areas of Africa where epidemics of konzo occur. Climate regimes are determined by modes of Pacific Decadal Oscillation, which modulates the ENSO. Study was done to determine the relationship of konzo epidemics to climate regimes and phases of ENSO, and to propose a model to explain while konzo epidemics do not occur in all drought affected areas. Data of all konzo epidemics in the past century and in DR Congo from 1974–1996, and indices of ENSO and PDO from 1915 to 2014 were obtained. Konzo epidemics were mapped to phases of ENSO and PDO. Wavelet spectral and wavelet spectral coherence analysis of climate indices and konzo epidemics were done. All konzo epidemics of the past century occurred during warm climate regimes. Of 19 warm phases of ENSO from 1974–1996 in DR Congo, 17 were coupled to konzo epidemics, while of 4 cold phases of ENSO, 1 was coupled to konzo epidemic, odds ratio 26 (95 % CI, 2–378). Global spectral of ENSO and konzo showed dominant periodicity of 5 years, while spectograms showed significant periodicities and coherence between 3–6 years. Spatial distribution of konzo is restricted to the area of maximal impact of El Nino on precipitation in Africa. El Nino is the underlying cause of konzo epidemics. Control of konzo epidemics requires management of the impact of El Nino on agriculture in areas where the population depends on cassava as sole source of calories during droughts. There is the need to develop forecast models of changes in cassava production to predict likely periods of konzo epidemics.